RESTAURANT XYZ PEAK HOUR WAITING TIME REDUCTION USING SIX SIGMA ANALYSIS - Evita Meiliana (Journal of Social and Economics Research, 2024)
This research analyzes the long waiting time experienced by customers of Restaurant XYZ during peak hours (Saturday-Sunday, 12:00PM-14:00PM and 17:00PM-19:00PM). The objective of this research is to find out the factors or root causes that contribute to the long waiting time. Apart from that, other objectives are also to identify, implement and evaluate effective strategies that can be used as a solution to optimize the ordering process system so that it can reduce the long waiting time experienced by XYZ Restaurant customers. Waiting time in this research is aimed at when customers queue to order food and beverage until the customer gets their food. The current waiting time that customers experience is 34 minutes. Meanwhile, Restaurant XYZ has a goal of reducing waiting time to 25 minutes. This target is determined by consideration of the customer and restaurant. To analyze, this research uses a combination of qualitative and quantitative approaches. The quantitative method will be used to collect data of ordering and queuing time directly through observation. Meanwhile the qualitative method will be used to collect the perceptions, experiences, and expectations of the company and customers through interviews. The qualitative data will be used as the benchmark and basis of the research analysis. With this approach, research will also adopt the DMAIC (Define, Measure, Analyze, Improve, Control) framework to identify problems, measure data, analyze data, generate solutions, and prepare control plans to maintain improvement. Overall, this research suggests changing the ordering system from Restaurant XYZ to a digital ordering system using a website which will reduce waiting time because the queue will change from physical to digital. Apart from that, this research also proposes some changes to integrate solutions and monitoring plans.